Ties that enable : community solidarity for people living with serious mental health problems - Scheid, Theresa L.; Smith, S. Megan (Rutgers University Press, 2021)
Ties that Enable is written for students, providers, and advocates seeking to understand how best to improve mental health care - be it for themselves, their loved ones, their clients, or for the wider community. The authors integrate their knowledge of mental health care as researchers, teachers, and advocates and rely on the experiences of people living with severe mental health problems to help understand the sources of community solidarity. Communities are the primary source of social solidarity, and given the diversity of communities, solutions to the problems faced by individuals living with severe mental health problems must start with community level initiatives. "Ties that Enable" examines the role of a faith-based community group in providing a sense of place and belonging as well as reinforcing a valued social identity. The authors argue that mental health reform efforts need to move beyond a focus on individual recovery to more complex understandings of the meaning of community care. In addition, mental health care needs to move from a medical model to a social model which sees the roots of mental illness and recovery as lying in society, not the individual. It is our society's inability to provide inclusive supportive environments which restrict the ability of individuals to recover. This book provides insights into how communities and system level reforms can promote justice and the higher ideals we aspire to as a society.